Emotional resilience and well-being in employability of nurses: a “Triangular Theory of Love’’ approach - George V. Joy; Abdulqadir J. Nashwan (Academia Mental Health & Well-Being)
This short communication explores the role of emotional resilience in the employability of nurses, utilizing Robert Sternberg’s Triangular Theory of Love to offer a distinctive perspective. This paper proposes that the components of love—intimacy, passion, and commitment—can be metaphorically associated with the qualities essential for resilience in nursing. It argues that these elements enhance nurses’ ability to handle the demands of their profession, thereby supporting their employability and well-being. The strategies highlighted include strengthening emotional support networks (intimacy), fostering engagement (passion), and promoting professional dedication (commitment). Applying Sternberg’s theory in this context provides a novel approach to understanding the intricacies of emotional resilience in the nursing field, suggesting that deeper emotional engagement in one’s work is vital for a resilient and fulfilling career.